2018
DOI: 10.1111/ggi.13312
|View full text |Cite
|
Sign up to set email alerts
|

Association between atherosclerosis and handgrip strength in non‐hypertensive populations in India and Japan

Abstract: AimAlthough several risk factors contribute to the development of sarcopenia, whether preclinical atherosclerosis contributes to the risk of sarcopenia is not established. The present cross‐sectional study aimed to investigate if there is an association between preclinical atherosclerosis and muscle strength among two ethnic populations.MethodsParticipants included individuals aged ≥40 years and enrolled in the third follow‐up examination of the Andhra Pradesh Children and Parents Study, India, and in the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…29 In fact, the brachial-ankle pulse wave velocity of patients with sarcopenia was higher than that of patients without sarcopenia among the patients without the history of cardiovascular disease (2101.7 [SD 307.8] cm/s vs 1874.9 [343.4] cm/s, P = 0.021 by the Mann-Whitney U-test), which is the same as previous studies. 17,30 Taken together, sarcopenia is associated with blood pressure variability.…”
Section: Discussionmentioning
confidence: 99%
“…29 In fact, the brachial-ankle pulse wave velocity of patients with sarcopenia was higher than that of patients without sarcopenia among the patients without the history of cardiovascular disease (2101.7 [SD 307.8] cm/s vs 1874.9 [343.4] cm/s, P = 0.021 by the Mann-Whitney U-test), which is the same as previous studies. 17,30 Taken together, sarcopenia is associated with blood pressure variability.…”
Section: Discussionmentioning
confidence: 99%
“…HS are proved to be associated with all-cause mortality and cardiovascular mortality [18,19]. Hirotomo Yamanashi et al reported arterial stiffness was associated with HS in nonhypertensive populations, but not in hypertensive populations [20]. Whereas, a long-term study result showed that there was no relation between HS and arterial stiffness [21].…”
Section: Discussionmentioning
confidence: 99%
“…HS are proved to be associated with all-cause mortality and cardiovascular mortality [18,19]. Hirotomo Yamanashi et al reported arterial stiffness was associated with HS in non-hypertensive populations, but not in hypertensive populations [20]. Whereas, a long-term study result showed that there was no relation between HS and arterial stiffness [21].…”
Section: Discussionmentioning
confidence: 99%